If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 5 = y + 26 Reorder the terms: 5 + 4y = y + 26 Reorder the terms: 5 + 4y = 26 + y Solving 5 + 4y = 26 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 5 + 4y + -1y = 26 + y + -1y Combine like terms: 4y + -1y = 3y 5 + 3y = 26 + y + -1y Combine like terms: y + -1y = 0 5 + 3y = 26 + 0 5 + 3y = 26 Add '-5' to each side of the equation. 5 + -5 + 3y = 26 + -5 Combine like terms: 5 + -5 = 0 0 + 3y = 26 + -5 3y = 26 + -5 Combine like terms: 26 + -5 = 21 3y = 21 Divide each side by '3'. y = 7 Simplifying y = 7
| 6(2-x)=9-2x+4+3x | | -7(p+7)+3(p-4)=-17 | | -4x+14=0 | | -5b+4=18 | | -4(x-y+8)= | | -14+n=-6 | | 5x-5=4x+23 | | -3a-7=2.3 | | 6x+6+13x+3=180 | | 1=X-.515 | | -(-2t)= | | .02X=.04 | | X-16=.08 | | 8v^6-18v-30=0 | | 3v^3+5v^2-18v-30=0 | | X-6=.48 | | 7+2x=2.5+.5x | | X+6=.52 | | 4x^2-4x=-2 | | X-4=.52 | | .6912+X=1 | | 3x-15x+26=-5x+10 | | 2x^2-(x+2)(x-3)=12 | | 11X=.01 | | 11X=-.13 | | -2x(x+3)-(x+1)(x-2)= | | 11X=W-.35 | | 20x+15y=1850 | | 6ab-8bc-4bd= | | 4x+8y=520 | | x(3+2)=2.7 | | -(6-5y)= |